PENDAMPINGAN HUKUM DAN EDUKASI HAK ASASI BAGI MASYARAKAT MARGINAL DI DESA GANDASULI - Pupu Sriwulan Sumaya (ICON Publisher, 2024)
The community service program with the theme of Legal Assistance and Human Rights Education for Marginalized Communities in Gandasuli Village aims to increase legal awareness and understanding of human rights (HAM) for marginalized community groups. This activity is motivated by the lack of access to information about law and human rights which can make marginalized communities in Gandasuli Village vulnerable to rights violations. The methods used in this program include legal counseling, focus group discussions (FGD), and direct legal consultations. The program is implemented in a participatory manner by involving local community leaders and non-governmental organizations to ensure that activities run effectively and sustainably. The results of this program show a significant increase in community understanding of human rights, basic rights as citizens, and legal mechanisms that can be used to protect these rights. In addition, the people of Gandasuli Village are also more proactive in conveying aspirations and complaints related to legal problems they face. The implications of this program are an increase in community empowerment in defending their rights before the law, as well as the potential for the formation of a sustainable legal care community in the future. The program also emphasizes the importance of collaboration between academics, legal practitioners, and the government in improving legal literacy among marginalized communities. Suggestions for follow-up activities include the need for in-depth training related to legal advocacy mechanisms and ongoing assistance so that communities can be more independent in dealing with complex legal problems. Thus, this service is expected to provide a long-term positive impact on protecting human rights among marginalized communities.